Immersive Technologies in the Educational Practice of Russian Universities - D. P. Ananin; A. Yu. Suvirova (Высшее образование в России, 2024)
Immersive technologies (ImT) are becoming more and more widespread in the R&D sector and more often in the academic agenda of higher education. The paper provides a systematic overview of the educational practices of Russian universities in the use of ImT in teaching. The study focuses on the institutional and didactic aspects of the ImT in Russian higher education. We interviewed representatives of Russian universities (N=16). The study presents the role of immersive educational technologies in the structure of an academic course and outlines the prospects for their further application. The cases of Russian universities evidence that immersive educational technologies are slowly finding their niche in higher and postgraduate education as a learning tool. Providing immersion of students in the real conditions of professional skills application, immersive educational products are designed to practice the algorithms of operations in standard and non-standard situations of their (future) occupations individually. Without changing the didactic structure of the academic course, immersive educational products occupy a place between the theoretical part and training practice. The authors conclude that immersive educational products have a great potential for development in terms of the visualization quality of educational material, integration of multimodal mode for group work, improvement of assessment scales and соnsideration of learning analytics. Given a range of positive effects (motivational, psychological, topological, developmental), the future of ImT in higher education depends on the legal regulation of their use in education, their availability to higher education institutions and the motivation of university teachers.